Entropy Generation Analysis of Human Thermal Stress Responses. (13th December 2012) - Boregowda, Satish C.; Choate, Robert E.; Handy, Rodney
Abstract : The present study involves application of an open system entropy generation formulation to analyze human thermal stress responses. The time-series human thermal stress response data are obtained by conducting a simulation using a validated finite-element human thermal model (FEHTM). These simulated human thermal response data are used as an input to the entropy generation expression to obtain human entropy generation (HEG) values. The effects of variables such as air temperature, relative humidity, physical activity, and clothing on entropy generation are examined. A design of experiment (DOE) approach is utilized to study the interaction effects of air temperature and relative humidity on entropy generation. The study establishes the importance and utility of entropy generation as a holistic measure of human thermal physiological reaction to external and internal changes. This novel study has great potential for use in military medicine, rehabilitation, sports, and related applications.